Treino com realidade virtual no alcance manual de crianças com paralisia cerebral: ensaio clínico randomizado cruzado - Nascimento, Natália Feitoza do (2015)
Introduction: The disability of upper limb function (MS) of children with Cerebral Palsy (CP) spastic hemiparetic restricts their participation in social activities. Virtual reality (VR) has shown promising results in functional recovery of this population, however, few studies have evaluated its effectiveness in the reaching of motion of these children. Objective: To assess the effects of training with RV in the movement range of children with CP spastic hemiparetic. Materials and Methods: We conducted a randomized crossover trial, where the sample consisted of 12 children diagnosed with PC hemiparetic, both genders, with a mean age of 9.63 ± 2.3 years. The sample characterization was performed by assessing muscle tone, range of motion, grip strength, functional performance, handicraft and desability. Kinematic analysis of the upper limb was performed by Qualisys Motion Capture System®. The study protocol consisted of two days of training and 1 revaluation. The training A (Nintendo Wii®) and B (standard protocol) were randomized the children in AB and BA sequences, with one week interval. Immediately kinematics pre and post-training was held and after a week. Data were analyzed using SPSS 20.0 (Statistical Package for Social Science) assigning a 5% significance level. The kinematic variables were analyzed by two-way ANOVA for repeated measures. Results and Discussion: No significant changes were observed for the angular variables and space-time between groups. The RV used for intervention to improve upper limb function in children with CP is still a relatively new method. Conclusion: Training with RV was not able to improve the reaching performance of children with cerebral palsy spastic hemiparetic.